Governing through financial markets: Towards a critical political economy of Capital Markets Union. (April 2018) - Braun, Benjamin; Gabor, Daniela; Hübner, Marina
Capital Markets Union is a large-scale political project to strengthen and further integrate European market-based finance. An initiative of the European Commission under Jean-Claude Juncker's leadership, Capital Markets Union seeks to realize a long-standing goal of European policy makers: a financial system in which capital markets will absorb more of citizens' savings and play a greater role in corporate finance. Market-based banking, too, is set to benefit from Capital Markets Union, which includes measures to revive the European securitization market. Given that market-based finance – or shadow banking – shouldered much of the blame for the financial crisis of 2007–2008, its resurgence as a policy priority of the European Union constitutes a puzzle. The present article lays the theoretical groundwork for a special issue that tackles this puzzle. It argues that rather than an end in itself, Capital Markets Union represents an exercise in 'governing through financial markets'. Pioneered in the United States, governing through financial markets is a political strategy adopted by state actors in pursuit of policy goals that exceed their institutional capacity.